Endpoints of Generalized Contractions in F-Metric Spaces with Application to Integral Equations. (6th June 2022) - Mlaiki, Nabil; Ahmad, Jamshaid; Al-Mazrooei, Abdullah Eqal
Abstract : The purpose of this article is to introduce locally α -ζ -multivalued contraction and rational Ćirić type α -ζ -multivalued contraction in the context of F -metric spaces and prove some endpoint results. We provide a nontrivial example to show the authenticity of our main result. Our results generalize some well-known results of literature. We also present some endpoint results in both graphic F -metric spaces and ordered F -metric spaces. As an application of our main result, we investigate the solution of an integral equation.